Mereduksi Waste pada Alur Perpindahan Material dengan Menggunakan Metode Value Stream Mapping di PT Hartono Istana Teknologi - Thomas Christopher Wong; Jani Rahardjo (Jurnal Titra, 2020)
PT Hartono Istana Teknologi manufactures LED TV by mapping production areas from support, BMS, final assembly and packing. One of their problem is in shipping. Sometimes, there are delay in shipping and the materials are more/less than it should be. It is suspected that there are some wastes that cause these problems. Therefore, the overall time datas are taken to see the cycle time, making value stream mapping to see the waste that occurs. After seeing the analysis, the problems are found, there are waste overprocessing, waste waiting, and waste inventory. To find the root of the problems are using tools cause & effect diagrams. Each settlement should be found to reduce the wastes. Minimizing wastes is expected to reduce excessive time in unpacking material, transfering material, checking materials in real time, reducing the delayed matterials shipping and reducing the operators.